2016
DOI: 10.1371/journal.pone.0145998
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Roles of NSP3 and Untranslated Regions in Rotavirus mRNA Translation

Abstract: Rotavirus NSP3 is a translational surrogate of the PABP-poly(A) complex for rotavirus mRNAs. To further explore the effects of NSP3 and untranslated regions (UTRs) on rotavirus mRNAs translation, we used a quantitative in vivo assay with simultaneous cytoplasmic NSP3 expression (wild-type or deletion mutant) and electroporated rotavirus-like and standard synthetic mRNAs. This assay shows that the last four GACC nucleotides of viral mRNA are essential for efficient translation and that both the NSP3 eIF4G- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…NSP3 also engages the scaffolding protein eIF4G, which, in turn, interacts with the cap binding protein eIF4E (41). In this way, rotavirus recapitulates the mRNA circularization that enables efficient translation (42)(43)(44)(45)(46). Like rotavirus mRNAs, reovirus mRNAs contain a conserved tetranucleotide sequence (CATC) at their 3= termini (7).…”
Section: Discussionmentioning
confidence: 99%
“…NSP3 also engages the scaffolding protein eIF4G, which, in turn, interacts with the cap binding protein eIF4E (41). In this way, rotavirus recapitulates the mRNA circularization that enables efficient translation (42)(43)(44)(45)(46). Like rotavirus mRNAs, reovirus mRNAs contain a conserved tetranucleotide sequence (CATC) at their 3= termini (7).…”
Section: Discussionmentioning
confidence: 99%
“…In both constructs, the nucleotide in position +4, which is not optimal in gs11 (U instead of G), was not changed. In a recent work with gs4 Gratia et al reported that optimisation of both positions -3 and +4 is important for expression efficiency [34]. However, the strong difference in expression of the two constructs with start codons sharing the same nucleotide context (GUG AUG U), strongly suggests that the IM inhibitory activity on translation cannot be ascribed to a less effective start codon recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Second, NSP3 inactivates eIF2 by stimulating its phosphorylation. [46] Efficient translation of rotavirus mRNA, which lacks the 3' poly(A) tail, does not require either of these factors. [47] NSP4 is a viral enterotoxin that induces diarrhoea and was the first viral enterotoxin discovered.…”
Section: Proteinsmentioning
confidence: 99%